Comparative Efficacy of Angiotensin Receptor-Neprilysin Inhibitors (ARNIs) vs. ACE Inhibitors in Heart Failure - Systemic Review and Meta Analysis - Virk, Ghazala S.; Hameed, Babar; Baloch, Zara; Mahmood, Arhum; Zubair, Hafsa; Rongali, Dinesh Aravind; Soliman, Abanoub; Naguib, Kerolos E.; Ahmed, Zubair; Mirza*, Muhammad Sohail S. (Cardiology and Cardiovascular Medicine, 2025)
Background: Angiotensin receptor-neprilysin inhibitors (ARNIs) have emerged as a singular therapeutic option for heart failure with decreased ejection fraction (HFrEF). This meta-analysis evaluates the efficacy and safety of ARNIs in comparison to ARBs and ACE inhibitors. Methods: A review of 12 studies concerning sufferers with HFrEF was conducted. Outcomes analyzed included cardiovascular mortality, heart failure hospitalizations, renal detrimental outcomes, left ventricular remodeling, and unfavourable events consisting of angioedema. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) had been calculated, and heterogeneity was assessed using I² information. Results: ARNI remedy substantially decreased cardiovascular mortality (OR 0.71, 95% CI 0.57–0.89, p = 0.002) and heart failure hospitalizations (OR 0.78, 95% CI 0.64–0.95, p = 0.01) compared to ACE inhibitors. Renal unfavorable consequences were marginally decreased (OR 0.76). ARNIs additionally tested advanced benefits in left ventricular remodeling and hypertrophy discount, even after brief-term follow-up. While angioedema hazard seemed to decrease with ARNIs, the effects were no longer statistically large (OR 0.62). Conclusions: This meta-analysis underscores the medical superiority of ARNIs in enhancing effects for HFrEF patients. Despite a few boundaries, along with heterogeneity in study layout and follow-up intervals, the findings help the early and sustained use of ARNIs as a cornerstone remedy in coronary heart failure control. Further studies are warranted to explore long-term advantages, cost-effectiveness, and broader affected person populations.